1999
DOI: 10.1088/0034-4885/62/10/201
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized criticality

Abstract: The concept of self-organized criticality was introduced to explain the behaviour of the sandpile model. In this model, particles are randomly dropped onto a square grid of boxes. When a box accumulates four particles they are redistributed to the four adjacent boxes or lost off the edge of the grid. Redistributions can lead to further instabilities with the possibility of more particles being lost from the grid, contributing to the size of each 'avalanche'. These model 'avalanches' satisfied a power-law frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
335
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(355 citation statements)
references
References 437 publications
17
335
0
3
Order By: Relevance
“…Here, the spatiotemporal power-law scaling strongly implies that the collective evolution through microcrack coalescence may be at a critical state [31,32]. Unlike sand-piles models, the driving force here is a newly nucleated microcrack per time-step from a prescribed distribution, which is randomly distributed in the lattice.…”
Section: Resultsmentioning
confidence: 98%
“…Here, the spatiotemporal power-law scaling strongly implies that the collective evolution through microcrack coalescence may be at a critical state [31,32]. Unlike sand-piles models, the driving force here is a newly nucleated microcrack per time-step from a prescribed distribution, which is randomly distributed in the lattice.…”
Section: Resultsmentioning
confidence: 98%
“…The scaling behavior of both the forest fire model and actual forest fires can be understood in terms of an inverse cascade model (11)(12)(13). This model is formulated in terms of individual trees on a grid and the clusters of trees that are generated.…”
Section: Cascade Modelmentioning
confidence: 99%
“…Perhaps the clearest previous observation of SOC is that of Moeur et al [7], who observed SOC in liquid 4 He near the equilibrium superfluid transition. By contrast, here SOC is observed near a nonequilibrium transition.…”
mentioning
confidence: 98%
“…SOC was first introduced by Bak, Tang and Wiesenfeld [3] as an explanation for the power-law behavior observed in some natural processes such as 1=f noise or avalanches in sandpiles. Since then, many theoretical and numerical models have been shown to exhibit SOC [2,4] but few physical realizations have been identified [2,[5][6][7][8][9][10]. An interesting path to SOC has been explained for systems exhibiting a nonequilibrium phase transition between fluctuating ''active'' steady states and nonfluctuating ''absorbing'' states from which the system cannot escape [2].…”
mentioning
confidence: 99%